2015
DOI: 10.5194/acp-15-10107-2015
|View full text |Cite
|
Sign up to set email alerts
|

Receptor modelling of both particle composition and size distribution from a background site in London, UK

Abstract: Abstract. Positive matrix factorisation (PMF) analysis was applied to PM10 chemical composition and particle number size distribution (NSD) data measured at an urban background site (North Kensington) in London, UK, for the whole of 2011 and 2012. The PMF analyses for these 2 years revealed six and four factors respectively which described seven sources or aerosol types. These included nucleation, traffic, urban background, secondary, fuel oil, marine and non-exhaust/crustal sources. Urban background, secondar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 42 publications
11
66
0
Order By: Relevance
“…The highest contributions of PNC were observed during the daytime, with two peaks, one the morning and one around noon during summer, and in the morning and the afternoon during the winter and transition months. Similar profiles and daily patterns have been also reported in London [44][45][46]; Los Angeles [47,48], and Venice [49]. The noon/afternoon peak is driven by the enhanced photochemistry whereas the morning peak is likely vehicular emissions that nucleate as the emissions dilute and cool [29,44].…”
Section: Nucleationsupporting
confidence: 72%
“…The highest contributions of PNC were observed during the daytime, with two peaks, one the morning and one around noon during summer, and in the morning and the afternoon during the winter and transition months. Similar profiles and daily patterns have been also reported in London [44][45][46]; Los Angeles [47,48], and Venice [49]. The noon/afternoon peak is driven by the enhanced photochemistry whereas the morning peak is likely vehicular emissions that nucleate as the emissions dilute and cool [29,44].…”
Section: Nucleationsupporting
confidence: 72%
“…For example, Charron and Harrison (2003) reported that particles in the range of 30-60 nm show a stronger association with light-duty traf- fic at a traffic hotspot in central London (Marylebone Rd); Janhäll et al (2004) reported an average particle size distribution peaking at 15-30 nm during morning peak high traffic intensity in the city of Göteborg (Sweden), which has a car fleet comparable to the UK; Ntziachristos et al (2007) found a sharp mode at 20-30 nm in sampling from engine exhausts. In addition, PMF factors with similar modal structures were found in other studies and were attributed to road traffic emissions: among others, Harrison et al (2011) linked a factor peaking at 20 nm to primary road traffic emissions near a major UK highway; Masiol et al (2016) measured PNSD in an international airport in northern Italy during summer and interpreted a factor with a clear mode at 35-40 nm as road traffic from the nearby city; Beddows et al (2015) and Vu et al (2016) found traffic factors with modal diameter at around 30 nm in an urban background site in London (North Kensington); Sowlat et al (2016) reported a factor peaking at 20-40 nm in number concentration and at around 30-40 nm in volume concentration in Los Angeles (US) and interpreted it as traffic tailpipe emissions. However, this factor lacks significant positive correlations with primary road traffic tracers (nitrogen oxides, eBC; Table 2), while other studies have reported weak positive correlations with such species Masiol et al, 2016;Vu et al, 2016;Sowlat et al, 2016).…”
Section: Warm Seasonmentioning
confidence: 82%
“…Their general characteristics have been reported in a number of studies (e.g. Alam et al, 2003;Charron et al, 2007Charron et al, , 2008Beddows et al, 2015;Vu et al, 2016) and can be summarised as follows: (i) particle modality at around 20 nm, (ii) higher frequency around noon in association with the peak in actinic flux intensities, (iii) clear seasonal cycles (higher average contribution levels in the summer, from June to September) and (iv) marked directionality from the westerly sectors, reflecting maritime atmospheric circulation regimes, with high wind speed and low PM 2.5 concentrations. A strong regional nucleation event occurred during the warm-period sampling campaign (starting on 7 September at 13:00 UTC and lasting for about 12 h).…”
Section: Analysis Of a Large Regional Nucleation Eventmentioning
confidence: 99%
“…Ma and Birmili (2015) reported that the annual contribution of traffic to the UFP number concentration was 7 %, 14 %, and 30 % at roadside, urban background, and rural sites, respectively, in and around Leipzig, Germany. On the other hand, traffic emissions contributed to 44 %-69 % of UFP concentrations in Barcelona (Pey et al, 2009;Dall'Osto et al, 2012;, 65 % in London (Harrison et al, 2011;Beddows et al, 2015), and 69 % in Helsinki (Wegner et al, 2012). Minguillón et al (2015) and Querol et al (2017) demonstrated that intensive NPF episodes take place inside the planetary boundary layer (PBL) in Barcelona, occurring around midday at surface level, when insolation and dilution of pollution are at their maxima.…”
Section: Introductionmentioning
confidence: 99%